Teaching English to Young Learners in pandemic era at SD Muslim Cendekia - Rahmania Rahmania; Peptia Asrining Tyas (Universitas Merdeka Malang, 2022)
The Covid-19 pandemic adds a new challenge for teachers to innovate new teaching strategies during the post-pandemic. Identifying English as a foreign language (EFL) students' learning strategies, teachers' preparation, and challenges are needed to innovate a new alternative approach for a post pandemic learning activity, thus investigating them is worth studying. The study is based on the premise that the golden age of young learners influences the success of language learning. This study was conducted during the government's implementation of English as a local supplementation subject. A case study was used as the approach of the study, with an interactive model to analyze the data. Observation, field notes, interviews, and documents are used as the instruments to collect the data. The result of this study shows that oral communication is the main component of the learning activity. A lesson plan is developed with the purpose of helping teachers establish the appropriate medium. The main issues encountered by teachers are how to capture students' attention and focus during the learning activity. In addition, suggestions for further study are presented.